BROGÅRD BACKWARDS: THE HIGH‐END GOLF LANDSCAPE AND THE MORPHOLOGY OF MANORIAL SPACE. Issue 4 (December 2015) - Jönsson, Erik
ABSTRACT: When Bro Hof Slott Golf Club – a high‐end, highprofile golf development in Upplands‐Bro, northwest of Stockholm – opened, the Brogård manor house became its clubhouse. Here a recent history of Bro Hof Slott as leisure space intermingles with a much longer history of Brogård as a landscape shaped through 400 years of nobility ownership. In place‐marketing and in short accounts, the estate's history is frequently reduced to merely a succession of names, sometimes combined with an appraisal of the scenic setting manorial ownership produced. The many hands, hooves and struggles historically shaping this landscape thus go missing, necessitating a more sustained focus on landscape morphology. How the estate landscape could be turned into an upmarket golf development is unintelligible without scrutinizing the nobility as a structuring force and the manorial landscape's current place in planning politics. Nobility power translated into extensive control of what could take place in the countryside. Brogård waschaped by crofters, tenant farmers and statare (labourers paid predominantly in kind) subordinate to the will of the estate owner, but also by all those processes resituating the nobility as class. Shaping the countryside, the nobility was in turn shaped by social movements, macro‐economic shifts and political decisions, together resulting in the particularities of the space now handled by municipal planning and appropriated to become Bro Hof Slott Golf Club. Through telling this story, I reconnect to a plea for acknowledging politics and political economy in analysing tourism and its spaces, while focus simultaneously lies on the dialectical entanglement of material landscape and its present‐day valuation.